The Knowledge and Competence of Professional Accountants Based on International Standards for Practitioners in Enterprises, Bang Kruai District, Nonthaburi Province - อุรัจฉัท, ทวิชชัย; รอดแจ่ม, ชุมพล (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The objectives of this research were to study and compare the level of knowledge and competency of professional accountants based on international standards for professional accountants in enterprises, Bang Kruai District, Nonthaburi Province 350 sample groups. Collected data by questionnaire. Data were analyzed using descriptive statistics included frequency, percentage, mean, and One-Way ANOVA. From the research results, it was found that professional accountants in enterprises, Bang Kruai District, Nonthaburi Province had high level of knowledge and competency based on international standards for practitioners in the enterprises. In the aspects of intellectual skills, academic, practical and functional skills, personal skills, interpersonal and communication skills, and organizational and business management skills all were also in a high level. The professional accountants in different general conditions of enterprises had different level of knowledge and competency with a statistical significance.